Bidirectional homeostatic regulation of a depression-related brain state by GABAergic deficits and ketamine treatment - Ren, Zhen (Biol Psychiatry, 2016)
BACKGROUND: Major depressive disorder (MDD) is increasingly recognized to involve functional deficits in both GABAergic and glutamatergic synaptic transmission. To elucidate the relationship between these phenotypes we made use of GABA(A) receptor γ2 subunit heterozygous (γ2(+/−)) mice, which we previously characterized as a model animal with construct, face and predictive validity for MDD. METHODS: To assess possible consequences of GABAergic deficits on glutamatergic transmission we quantitated the cell surface expression of NMDA- and AMPA-type glutamate receptors and the function of synapses in the hippocampus and medial prefrontal cortex of γ2(+/−) mice. In addition, we analyzed the effects of an acute dose of the experimental antidepressant ketamine on all these parameters in γ2(+/−) vs. wild-type mice. RESULTS: Modest defects in GABAergic synaptic transmission of γ2(+/−) mice resulted in a strikingly prominent homeostatic-like reduction in the cell surface expression of NMDA- and AMPA-type glutamate receptors, along with prominent functional impairment of glutamatergic synapses in the hippocampus and medial prefrontal cortex (mPFC). A single subanesthetic dose of ketamine lastingly normalized the glutamate receptor expression and synaptic function of γ2(+/−) mice to wild-type levels, along with antidepressant-like behavioral consequences selectively in γ2(+/−) mice. GABAergic synapses of γ2(+/−) mice were potentiated by ketamine in parallel but only in mPFC. CONCLUSIONS: Depressive-like brain states that are caused by GABAergic deficits involve a homeostatic-like reduction of glutamatergic transmission that is reversible by an acute, subanesthetic dose of ketamine, along with regionally selective potentiation of GABAergic synapses. The data merge the GABAergic and glutamatergic deficit hypothesis of MDD.